Culturally competent health care for sex workers: an examination of myths that stigmatize sex work and hinder access to care. Issue 3 (3rd July 2019) - Sawicki, Danielle A.; Meffert, Brienna N.; Read, Kate; Heinz, Adrienne J.
Abstract: Sex workers are individuals who offer sexual services in exchange for compensation (i.e. money, goods, or other services). Within the United States, the full-service sex work (FSSW) industry generates 14 billion dollars annually there are estimated to be 1–2 million FSSWers, though experts believe this number to be an underestimate. Many FSSWers face the possibility of violence, legal involvement, and social stigmatization. As a result, this population experiences increased risk for mental health disorders. Given these risks and vulnerabilities, FSSWers stand to benefit from receiving mental health care however a constellation of individual, organizational, and systemic barriers limit care utilization. Destigmatization of FSSW and offering of culturally competent mental health care can help empower this traditionally marginalized population. The objective of the current review is to (1) educate clinicians on sex work and describe the unique struggles faced by FSSW and vulnerability factors clinicians must consider, (2) address five common myths about FSSW that perpetuate stigma, and (3) advance a research and culturally competent clinical training agenda that can optimize mental health care engagement and utilization within the sex work community.